Implementation science in perioperative care - Lane-Fall, Meghan B. (Anesthesiol Clin, 2018)
There is a 17-year gap between the initial publication of scientific evidence and its uptake into widespread practice in healthcare. The field of implementation science (IS) emerged in the 1990s as an answer to this “evidence-to-practice gap.” In this paper, we present an overview of implementation science, focusing on the application of IS principles to perioperative care. We describe opportunities for additional training and discuss strategies for funding and publishing IS work. The objective of this discussion is to demonstrate how IS can improve perioperative patient care, while highlighting perioperative IS studies and identifying areas in need of additional investigation.